Pendidikan Pra Nikah Sebagai Upaya Meminimalisir Perceraian (Studi Model Kursus Pra Nikah di Kementerian Agama Kabupaten Tegal) - Muhammad Fatkhudin (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2019)
This paper presents the results of research on Pre-Marriage Education in the Pre-Marriage Course model in Tegal Regency, the implementation of the Pre-Marriage Course in broad outline refers to Perdirjen No. DJ.II / 491/2009. The implementation of Pre-Marriage Courses is generally carried out according to the capabilities of the KUA and the Ministry of Religion. The model of implementation, both in groups and with individuals is carried out in accordance with the event of marriage and the willingness of the bride and groom. The speakers came from the KUA more often, the material presented was related to government regulations related to marriage, marriage law, household matters, and remembrance of the reconciliation process which will be carried out by Catin during the wedding procession, and the duration of the group is approximately 3 hours and 1 hour individual. Broadly speaking, the implementation of the Pre-Marriage Course has embraced the principle of public service (Law No. 25/2009), except that in the professional principle it cannot be fulfilled because it collides with the funding owned by the Ministry of Religion. Tulisan ini menyajikan hasil penelitian tentang Pendidikan Pra Nikah model Kursus Pra Nikah di Kabupaten Tegal, penyelenggaraan Kursus Pra Nikah secara garis besar mengacu pada Perdirjen No. DJ.II/491/2009. Penyelenggaraan Kursus Pra Nikah secara umum dilakukan sesuai kemampuan dari KUA dan Kementerian Agama. Model penyelenggaraan, baik secara kelompok maupun dengan perorangan dilakukan sesuai dengan peristiwa nikah dan kesediaan calon pengantin. Narasumber lebih sering berasal dari pihak KUA, materi yang disampaikan menyangkut masalah peraturan pemerintah terkait perkawinan, hukum pernikahan, perihal berumah tangga, dan pengingatan kembali proses ijab qabul yang nanti akan dilakukan catin saat melakukan prosesi pernikahan, dan durasi penyelenggaraan secara kelompok kurang lebih 3 jam dan perorangan 1 jam. Secara garis besar, penyelenggaraan Kursus Pra Nikah sudah menganut asas pelayanan publik (UU No. 25/2009), hanya saja pada asas profesional belum bisa dipenuhi karena berbenturan dengan pendanaan yang dimiliki Kementerian Agama.